2017
DOI: 10.1371/journal.ppat.1006417
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus persists in the presence of a type III interferon response

Abstract: The RIG-I-like RNA helicase (RLR)-mediated interferon (IFN) response plays a pivotal role in the hepatic antiviral immunity. The hepatitis A virus (HAV) and the hepatitis C virus (HCV) counter this response by encoding a viral protease that cleaves the mitochondria antiviral signaling protein (MAVS), a common signaling adaptor for RLRs. However, a third hepatotropic RNA virus, the hepatitis E virus (HEV), does not appear to encode a functional protease yet persists in infected cells. We investigated HEV-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 61 publications
10
100
0
1
Order By: Relevance
“…In immunocompromised patients, chronic infection has been widely reported, which is conceivably attributed to compromised innate and adaptive immunity . Consistently, a recent study reported that persistent HEV infection in cell culture does not activate type I IFN, although it was accompanied by a type III IFN response . In our study, we found that HEV RNA activates both type I and type III IFN responses, resulting in potent antiviral effects, which more likely reflected the infection phase with active virus–host interactions in HEV patients.…”
Section: Discussionsupporting
confidence: 88%
“…In immunocompromised patients, chronic infection has been widely reported, which is conceivably attributed to compromised innate and adaptive immunity . Consistently, a recent study reported that persistent HEV infection in cell culture does not activate type I IFN, although it was accompanied by a type III IFN response . In our study, we found that HEV RNA activates both type I and type III IFN responses, resulting in potent antiviral effects, which more likely reflected the infection phase with active virus–host interactions in HEV patients.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests they have functional roles in HEV sensing and activation of the downstream anti‐viral signaling pathway . Consistently, inhibition of IRF3 phosphorylation, the key downstream signaling pathway of TLR3, RIG‐I and MDA5, notably increases HEV replication …”
Section: Innate Immunity Against Hevmentioning
confidence: 70%
“…RIG‐I and MDA5 are involved in the HEV‐induced IFN response . HEV induces predominantly a type III IFN response, rather than a type I IFN, to control viral growth .…”
Section: Innate Immunity Against Hevmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of IFN subtypes, RIG-I activates two distinct categories of ISGs, one JAK-STAT-dependent and the other JAK-STAT-independent, which coordinately contribute to the antiviral immune response to HEV infection [92]. However, persistent activation of the JAK-STAT-dependent signaling pathway enables HEV-infected cells to resist exogenous IFN treatment, while the depletion of IFN-λ receptors or MAVS (mitochondria antiviral signaling protein) resorts to the antiviral immune response induced by IFN, suggesting that the persistent presence of IFN-λ benefits the establishment of HEV infection [93]. Together with a recent report of antiviral immune activities mediated by IFN-λ, we still lack important pieces of information on basic IFN-λ functions.…”
Section: Future Trends Of Application For Clinical Treatmentmentioning
confidence: 99%